Machine Identity Management in Modern Enterprise Security: Concepts, Challenges, and the Role of Privileged Access Management Systems - Yilmaz, Erhan (Engineering, Technology & Applied Science Research, 2026)
The rapid expansion of non-human entities across cloud platforms, microservices, IoT/OT devices, and automated deployment pipelines has positioned machine identities as a main element of enterprise security. These identities, instantiated through cryptographic credentials, such as certificates, SSH keys, and API tokens, enable authentication, authorization, confidentiality, and accountability in Machine-to-Machine (M2M) communication. However, their scale, high turnover, and architectural heterogeneity have outpaced traditional identity governance practices, leading to credential sprawl, inconsistent lifecycle management, and ineffective revocation mechanisms. This study examines the conceptual foundations and lifecycle requirements of machine identities, synthesizing recent research on certificate and key management in distributed environments. It evaluates the evolving role of Privileged Access Management (PAM) systems as policy-driven orchestration and governance layers for machine identities, particularly within zero-trust architectures. The analysis highlights both the strengths and limitations of current PAM implementations, identifying key research directions that include context-aware lifecycle automation, behavioral and attestation-based identity validation, governance for autonomous agents, and post-quantum secure identity infrastructures. Strengthening machine identity governance is, therefore, critical for ensuring the security and operational resilience of contemporary enterprise systems.